EFFECT OF LIGHT INTENSITY ON THE CELL DENSITY, DIAMETER AND CELL VOLUME ZOOXANTHELLAE FROM ISOLATE SOFTCORAL Zoanthus sp - Suliswati Suliswati; Esti Harpeni; Moh. Muhaemin (AQUASAINS, 2016)
Coral reefs are one of the aquatic ecosystem trophic productive for aquatic organisms. Coral reefs can not be separated from the various threat of causing damage. Physiological damage that is visible coral bleaching. Bleaching of coral reefs due to causes it may be the biggest threat to coral ecosystems due to widespread in various regions. Coral bleaching causing the loss of endosymbiont coral or reduction of photosynthetic pigments zooxanthellae of corals. Zooxanthellae need light for photosynthesis. The process will produce energy which serves for the biosynthesis cell, growth and cell division. Therefore light plays an important role in the process of photosynthesis. This research aims were to know the cell density, diameter and volume zooxanthellae cells on different light intensity. The research was conducted on July-August 2016, in the Aquaculture Laboratory, Program Study of Aquaculture Faculty of Agriculture University of Lampung. Observed parameters were the density, diameter and volume zooxanthellae cells. Research used the 4 treatments and 5 replications namely 3800 lux (IC1), 6250 lux (IC2), 7980 lux (IC3), and 11800 lux (IC4). Measurement of the density and diameter of zooxanthellae cells used a hemocytometer neubauer improved and objective micrometer (0.01 mm). Data were analyzed by analysis of variance (ANOVA) and followed by LSD test. The results showed that the intensity of light significantly affected the density, diameter and volume zooxanthellae cells. Intensity light given by zooxanthellae responded with increased density and a decrease the diameter and volume zooxanthellae cells in the early stages of culture (0-18 hours).